2010
DOI: 10.1093/jrs/feq012
|View full text |Cite
|
Sign up to set email alerts
|

Mental and Physical Health Consequences of Repatriation for Vietnamese Returnees: A Natural Experiment Approach

Abstract: While there is much speculation about the potential consequences of repatriation, systematic comparisons of health outcomes employing standard measures and appropriate population-based samples of migration returnees and non-returnees are virtually non-existent. This study addresses this significant gap in the empirical literature by employing standard measures of mental and physical health outcomes for comparable samples of repatriated international migration returnees now living in Ho Chi Minh City; never-lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 35 publications
0
31
0
1
Order By: Relevance
“…The results on patterns of harmful alcohol use are summarised in Table 1 among adults ranged from 5.5% among Burmese male refugees in Thailand to 17% among Vietnamese refugees who repatriated back to Vietnam. (Fu & Van Landingham, 2010) A study of IDPs in Georgia found that 12% of men and 2% of women were classified as engaging in episodic heavy drinking (more than 60 grams of pure alcohol per drinking session in the past seven days). Alcohol use in adolescents (aged <18 years) was reported from seven studies.…”
Section: Patterns Of Harmful Alcohol Usementioning
confidence: 99%
See 2 more Smart Citations
“…The results on patterns of harmful alcohol use are summarised in Table 1 among adults ranged from 5.5% among Burmese male refugees in Thailand to 17% among Vietnamese refugees who repatriated back to Vietnam. (Fu & Van Landingham, 2010) A study of IDPs in Georgia found that 12% of men and 2% of women were classified as engaging in episodic heavy drinking (more than 60 grams of pure alcohol per drinking session in the past seven days). Alcohol use in adolescents (aged <18 years) was reported from seven studies.…”
Section: Patterns Of Harmful Alcohol Usementioning
confidence: 99%
“…One study with Vietnamese returnees found no significant association. (Fu & Van Landingham, 2010) Two studies examined the influence of education level and harmful alcohol use. (Fu & Van Landingham, 2010; Jordans, Murphy, A study of Bhutanese refugees in Nepal found that higher educational status had a protective effect on harmful alcohol use, while the study with Vietnamese returnees found no significant association between education level and harmful alcohol use.…”
Section: Demographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that programs which offer assistance immediately upon return are more likely to benefit returnees because they reinforce a sense of safety and belonging (Ruben et al, 2009). Although many different kinds of assistance programs exist, return migrants report feeling let down by their institutions and highlight the lack of services to assist with resettlement and reintegration (Fu & Vanlandingham, 2010;Gillespie et al, 2009). Of specific concern, many repatriation programs provide limited information about living conditions in the country of origin.…”
Section: )mentioning
confidence: 99%
“…Migration often exposes returnees to particular health risks, while limiting the resources needed to address these risks (Collinson, 2010). For example, living conditions while awaiting asylum, length of stay in a host country, access to health services upon return, as well as the migration journey itself can impact health (Fu & Vanlandingham, 2010;Hasanovic, Sinanovic, & Pavlovic, 2005;von Lersner et al, 2008).…”
Section: )mentioning
confidence: 99%